A one-dimensional BaI2 chain with five- and six-coordination, formed within a single-walled carbon nanotube - Sloan, J; Grosvenor, S; Friedrichs, S; Kirkland, A; Hutchison, J; Green, M (2002)
Unknown in bulk BaI2: Ba coordination numbers of 5 and 6 are present in the one-dimensional (1D) crystal chains formed by BaI2 within single-walled carbon nanotubes (SWNTs). This is revealed by high-resolution transmission electron microscopy images (I). The derived structure model II shows the bond angles measured for equatorial BaI4 units along the central 1D octahedral chain within the BaI2 chain in an SWNT capillary.